MODERN DETERMINANTS OF FOREIGN INVESTMENT’ ACTIVATION IN THE INTERNATIONAL FINANCE AREA - LESHCHENKO, Maryna; PASENKO, Vladyslav; SAKHNO, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article defines the modern determinants of foreign investments’ activation in the international financial space. Foreign investments became a decisive driver for the formation of additional competitive advantages in the global capital market, ensuring the transfer of capital, knowledge, and technologies across borders. Foreign investment flows become the basis for forming a single system of relations and a new configuration of the world economy. The dynamics of foreign direct investment (FDI) by groups of countries and regions were analyzed. Over the past two decades, global FDI flows have grown rapidly, largely due to the intensification of investment activity in developing countries due to accelerating economic growth, increasing market potential, and using effective government policy tools to stimulate foreign investment. The specifics of the distribution of foreign direct investment between host countries have been determined in view of the consequences of the COVID-19 pandemic. The pandemic didn’t affect the countries’ ranking among the leaders in attracting and exporting FDI. Due to the export of FDI from Hong Kong (China) and Thailand, Asia became the only region where growth in FDI flows was recorded during the pandemic, and China became the largest investor in the world in 2020. As a result of quarantine restrictions and measures to counter the consequences of the pandemic, the lowest fall in FDI indicators over the last decade. The fact that the number of restrictive measures against foreign capital in 2022 increased sharply, mainly due to the war in Ukraine has been determined. Such procedures included sanctions against financial institutions; trade and transportation restriction measures; travel bans and asset freezes for hundreds of individuals and legal entities. The peculiarities of the recovery of FDI indicators in the post-Covid period are highlighted, and it is determined that in the near future, new risks may arise for the stable development of international investment activities in view of the war in Ukraine and a number of new shocks in the world economy.
Keywords: foreign investments; dynamics; trends; developed countries; developing countries; regional distribution; the COVID-19 pandemic; limitation; risks